Corpus Analysis of the Subject’s Epistemic Position in English Dialogical Discourse - Shubko, Viktoriia (Linguistic and Conceptual Worldviews, 2022)
The given article is devoted to highlighting the functions of the epistemic verb to know as a marker of the self-position of the subject in the artistic dialogic discourse on the material of the works by D.H. Lawrence. The epistemic self-position reflects the subject's knowledge of the world, his worldview, his points of view and his beliefs. It refers to the speaker's knowledge of the subject of speech, the degree of confidence in expression. Modern corpus-oriented studies of discourse are performed in three directions, namely, textual (study of the choice of language units, meanings and models in texts); critical (combination of critical discourse analysis and system functional linguistics); contextual (taking into account situational factors of communication, involvement of the theory of speech acts and pragmatics). Due to the explanatory inflexibility of the existing electronic corpora of the English language, that is the impossibility of a complete analysis of the presented contexts, our own corpus of texts was created to study the epistemic position of a subject in English dialogic discourse. It has been illustrated by the example of the works by David Herbert Lawrence, one of the key English writers of the early twentieth century. We have singled out and framed the contexts of the use of epistemic verbs (such as, know, think, seem, believe, understand, suppose, guess, expect, hope). The selected contexts of the use of epistemic verbs in artistic dialogic discourse will be analyzed in semantic and pragmatic aspects, namely - the meaning of the studied epistemic markers, such as reliability, faith, confidence, etc., and their pragmatic usage to express strategies and tactics of I-concept. The perspective of this study is a detailed analysis of the semantic and pragmatic features of epistemic markers in artistic discourse.
Keywords: discourse, epistemic position, epistemic markers, corpus analysis